M= (2x-5) (2x+5) +125 tại x=10
M = ( 2x - 5 ) ( 2x + 5 ) +125
= ( 2x )^2 - 5^2 + 125
= 4x^2 - 25 + 125
= 4 * 100 + 100
= 500
`M = (2x-5)(2x+5)+125`
`-> M =(2x)^2 - 5^2 +125`
`->M = 4x^2 - 25+125`
`->M = 4x^2+100`
`->M=4 . 10^2 +100`
`->M=4.100 +100`
`->M=400+100`
`-> M=500`
Vậy `M=500` khi `x=10`
`M = (2x-5)(2x+5) + 125`
`->M = (2x)^2 - 5^2 + 125`
`-> M = 4x^2 - 25+125`
`-> M = 4x^2 + 100`
Thay `x=10` vào ta được :
`->M = 4 . 10^2 +100`
`-> M = 4 . 100 + 100`
`-> M=400 + 100`
`-> M=500`
Vậy `M=500` khi `x=10`